1976
DOI: 10.1136/jcp.29.10.941
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the production of enterotoxins by Bacillus cereus.

Abstract: SYNOPSIS Evidence is presented for the existence of three distinct enterotoxins detected in concentrated cell-free culture filtrates of selected Bacillus cereus strains. The first was a product capable of stimulating the adenylate cyclase-cyclic-AMP system in intestinal epithelial cells and, possibly through this, causing fluid accumulation in ligated ileal sections ('loops') of young rabbits. This was elaborated by a strain isolated from an incident of diarrhoea and which caused diarrhoea in 6 of 10 monkey fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…On the other hand, Thompson e t al. (1984) found experimental evidence for a probable multicomponent or subunit enterotoxin structure. Three antigenic components were identified by chromatographic separation of extracellular proteins produced by B. cerem B-4ac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Thompson e t al. (1984) found experimental evidence for a probable multicomponent or subunit enterotoxin structure. Three antigenic components were identified by chromatographic separation of extracellular proteins produced by B. cerem B-4ac.…”
Section: Discussionmentioning
confidence: 99%
“…This organism causes two different types of human gastroenteritis (Turnbull, 1976 ;Turnbull e t al., 1979b). The ability of B. cereuJ to cause diarrhoea is attributed to the production of an enterotoxin (B. cerem diarrhoeal enterotoxin, designated bc-D-ENT in this study) (Gilbert & Kramer, 1984;Turnbull, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The results from an examination of the three strains used in the feeding trials are shown in from recent work (Turnbull, 1976) that strains which actually produce diarrhoea exhibit the ability to stimulate adenylate cyclase activity as well as giving loop positives. Strain 2532B did not stimulate adenylcyclase activity, but strain 4433 did.…”
Section: Ligated Rabbit Ileal Assaysmentioning
confidence: 99%
“…Cereulideproducing B. cereus isolates are frequently reported in processed foods, implicated (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) or not implicated (17)(18)(19)(20)(21) with foodborne illness, but appear infrequently in farming or natural outdoor environments (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%